Potensi Penerapan STEAM dalam Pembelajaran Pencemaran Lingkungan - Musyafiatun Musyafiatun; Muhammad Syaipul Hayat (Perkumpulan Kualitama Edukatika Indonesia, 2022)
This study aims to analyze the potential application of STEAM (Science, Technology, Engineering, Art, Mathematics) in environmental pollution learning at MTs Negeri 3 Demak. This research is a type of descriptive qualitative research. Data collection techniques using observations and questionnaires about the potential application of STEAM in learning environmental pollution. The type of sampling used in this research is cluster random sampling, which is the sampling technique with certain considerations. The data collection method used the documentation analysis method so that the researchers analyzed the documents resulting from the research questionnaire. The data analysis method used is the Miles and Huberman model starting with data collection, data presentation, data reduction, conclusion drawing and verification. The population is science teachers throughout Demak district, totaling 135 teachers, with 24 teachers as the sample. The results showed that there were 62.5% of teachers who understood STEAM. There are 25% of teachers who have applied STEAM. Eligibility to use STEAM was given 83.3%. The data above shows that the application of STEAM at the SMP or MTs level has the potential to improve the quality of learning outcomes.